Durability performance of lightweight concrete containing oil palm ash subjected to air curing - Nurul Syammimi, Zulkaranai Hassan (2018)
Cement manufacturing industry and solid waste disposal from palm oil industry in Malaysia had caused a bad impact towards the environment. The production of cement produces high amount of carbon dioxide emission while the disposal of palm oil waste such as oil palm ash (OPA) and palm oil boiler stone (POBS) are rather be disposed in landfills without profit return. This has made the palm oil waste as a source of material to partially replace the cement content in the concrete mix as to reduce the environmental pollution and amount of waste being disposed. Moreover, the use of POBS as course aggregate replacement in concrete can perpetuate the natural resources such as granite. Hence, a research to study the durability performance of lightweight concrete (LWC) containing oil palm ash as partial cement replacement that is subjected to air curing is made for 23 weeks. In fact, LWC containing OPA exhibits low water absorption as it is high in pozzolanic reaction. This study also emphasized the durability performance in terms of both acid and sulphate resistance towards LWC. Trial mix is made in the early stage of concrete mix design to select the best performing OPA lightweight concrete while taking account into durability and strength. As such, concrete Grade 60 with 20% of OPA as partial cement replacement is the best mix to sustain acid and sulphate attacks with a great durability and strength. All in all, this study proves that LWC containing OPA is potentially be applied in construction industry for structural application as it can minimize the cost of production while at the same time reduces the dead load of concrete structure.